ACCESSIBILITY AND ADAPTABILITY OF EMERGING TECHNOLOGY AMONG MOBILE WALLET CUSTOMERS USING TAM MODEL - M, Thirupathi; G, Vinayagamoorthi; S, Gopalakrishnan; V.P, Sriram; S, Kavitha. (The journal of contemporary issues in business and government, 2021)
Mobile wallet payment is a massive and unique advanced Technology platform to make cashless payments around the world. In a developing country like India, the adoption of advanced technology is more essential and it is also a part of economic development. The mobile wallet payment system and financial inclusions are part of the economic growth of the country. This study develops a conceptual model to determine the factors influencing adopting the mobile wallet payment and financial inclusion. The study aims to check the technology acceptance of cashless payment and mobile wallet in the Indian scenario. Apart from the Technology, Safety, and Social factors of TAM and UTAUT models, this study introduces two additional factors namely economic factors and Government insisting factors to analyze the adaptation of mobile wallets in Tamil Nadu.We found in this study that, the Government of India has predominantly insisted on the people to adopt the mobile wallet/ cashless payment in India. Even though the factors influence, the actual benefit of the mobile wallet is priceless and makes the customers very much comfortable to transfer the funds. This study also analyzes the risk and security issues of mobile wallets and how the customers are mentally disturbed at the time of using mobile wallet payments, and we brought a strong recommendation to overcome the issues.